Old Foe, New Host: Epidemiology, Genetic Diversity, and Pathogenic Characterization of Maize Streak Virus in Rice Fields from Burkina Faso - Noun Magdy Ibrahim Fouad; Mariam Barro; Martine Bangratz; Drissa Sérémé; Denis Filloux; Emmanuel Fernandez; Charlotte Julian; Nignan Saïbou; Abalo Itolou Kassankogno; Abdoul Kader Guigma; Philippe Roumagnac; Issa Wonni; et al. (Phytobiomes Journal)
Rice is of critical significance regarding food security worldwide, including in Africa. Only two viruses impacting rice production in Africa have been deeply investigated for decades: the rice yellow mottle virus (Solemoviridae) and the rice stripe necrosis virus (Benyviridae). Using viral metagenomics, we aimed at broadening knowledge on interacting communities associated with plants in rice landscapes and exploring the diversity and epidemiological status of viruses circulating in rice fields from Burkina Faso. We performed an epidemiological survey in this country between 2016 and 2019 involving 57 small farmers’ rice fields under two production systems: rainfed lowlands and irrigated areas. More than 2,700 rice samples were collected without regard to disease symptoms following a regular scheme. Wild and cultivated Poaceae (maize and sugarcane) growing in nearby rice fields were also collected. Unexpectedly, metagenomics detected maize streak virus (MSV) (Geminiviridae) in analyzed rice samples. Further molecular analyses using rolling circle amplification-polymerase chain reaction showed that MSV was widely distributed and highly prevalent in both rainfed lowlands and irrigated rice areas. MSV-A and MSV-G strains were identified. MSV-G, exclusively identified thus far in wild grasses, was the most prevalent strain, whereas MSV-A, known to cause severe symptoms in maize, was sporadically identified. Using infectious clones in experimental conditions, we confirmed the pathogenicity of both MSV strains in rice. Thus, in addition to contributing to the epidemiological surveillance of rice production in Africa, our results illuminate new epidemiological and pathogenic aspects of one of the most studied plant viruses with significant economic consequences in Africa. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.